Dopaminergic lesioning impairs adult hippocampal neurogenesis by distinct modification of α‐synuclein. Issue 1 (9th October 2015) - Schlachetzki, Johannes C.M.; Grimm, Thomas; Schlachetzki, Zinayida; Ben Abdallah, Nada M.B.; Ettle, Benjamin; Vöhringer, Patrizia; Ferger, Boris; Winner, Beate; Nuber, Silke; Winkler, Jürgen
Abstract : Nonmotor symptoms of cognitive and affective nature are present in premotor and motor stages of Parkinson's disease (PD). Neurogenesis, the generation of new neurons, persists throughout the mammalian life span in the hippocampal dentate gyrus. Adult hippocampal neurogenesis may be severely affected in the course of PD, accounting for some of the neuropsychiatric symptoms such as depression and cognitive impairment. Two important PD‐related pathogenic factors have separately been attributed to contribute to both PD and adult hippocampal neurogenesis: dopamine depletion and accumulation of α‐synuclein (α‐syn). In the acute 1‐methyl‐4‐phenyl‐1, 2, 3, 6‐tetrahydropyridine model, altered neurogenesis has been linked merely to a reduced dopamine level. Here, we seek to determine whether a distinct endogenous α‐syn expression pattern is associated, possibly contributing to the hippocampal neurogenic deficit. We observed a persistent reduction of striatal dopamine and a loss of tyrosine hydroxylase‐expressing neurons in the substantia nigra pars compacta in contrast to a complete recovery of tyrosine hydroxylase‐immunoreactive dopaminergic fibers within the striatum. However, dopamine levels in the hippocampus were significantly decreased. Survival of newly generated neurons was significantly reduced and paralleled by an accumulation of truncated, membrane‐associated, insoluble α‐syn within the hippocampus. Specifically, the presence of truncated α‐syn species was accompanied by increased activity of calpain‐1, a calcium‐dependent protease. Our results further substantiate the broad effects of dopamine loss in PD‐susceptible brain nuclei, gradually involved in the PD course. Our findings also indicate a detrimental synergistic interplay between dopamine depletion and posttranslational modification of α‐syn, contributing to impaired hippocampal plasticity in PD. © 2015 Wiley Periodicals, Inc. Abstract : Although soluble α‐synuclein (α‐syn) level within the hippocampus is not altered, C‐terminal‐truncated α‐syn and insoluble α‐syn levels are significantly increased after injection of MPTP.